Design and fabrication of ankle-foot orthoses through 3D scanning and rapid prototyping - Engku Ersyad, Engku Abas (2013)
This project aims to tackle the problem of current manufacturing method of production Ankle-Foot Orthoses (AFO). AFO is needed for people who experience foot-drop, limited ability or inability to raise the foot at the ankle joint. There are two ways of acquiring these AFOs, first is by getting on the shelves, prefabricated AFO, which are affordable and designed to fit a range of patients. However, due to this features, it will not provide individualized comfort and functionality. Second method of obtaining AFO is by using traditional custom-made technique which is laborious and time-consuming manual process and can only be accomplished by expert orthotists. Nonetheless it does provide better fit and function. This research explore the possibilities of using current technology in bring the manufacturing process of AFO much faster and reliable. By using 3D scanner to obtain the geometric data of the foot, the process of fabricating patient-specific orthotic devices has the potential to deliver outstanding comfort due to the accurate polygon data. The process of designing orthoses using reverse engineering software would permit changes in the standard design to meet the exact needs of each patient. In order to test the effectiveness of the AFO made using the new modern method, gait analysis was conducted and comparison was made. It was concluded that the fabricated able to perform its intended function which is to restrict ankle motion and prevent drop-foot symptoms. The design made based on the scanned cloud point data also prove to fit excellently and comfortably on the subject’s foot using velcro strap.